Chaos and life : complexity and order in evolution and thought - Bird, R. J. (Richard J.) (Columbia University Press, 2003)
An alternative view of evolving complexity. Bird argues that randomness means not disorder but infinite order and that complexity arises from the "playing out" of chaotic systems.